Os saberes e fazeres de Aglaé D’Ávila Fontes : uma educadora e mediadora cultural sergipana (1955-2005) - Monteiro, Rísia Rodrigues Silva (2021)
This thesis investigates the activity of the intellectual Aglaé d’Ávila Fontes as an educator and cultural mediator from Sergipe. The teacher was part of the implementation of the Creativity Center and directed it for three administrations; she has created theater groups, written books and plays; she is a researcher of popular culture from Sergipe; was a professor at Federal University of Sergipe (UFS); is a member of the Academy of Letters of Sergipe and the Academy of Letters of Lagarto; took on the presidency of the Historical and Geographical Institute of Sergipe, in 2008, and was reappointed to it in 2020, for the three-year term 2021 to 2023. The general goal of this research is to understand the contribution of Aglaé Fontes as an educator and a cultural mediator intellectual for the state, highlighting the three axes of her activity: the intellectual producer; the mediator of popular culture; and the director and arteducator at Creativity Center, built in Aracaju, Sergipe’s capital, in 1985. This investigation outlined as specific goals: to identify how the trajectory of Aglaé Fontes was inserted in the educational and cultural areas of the state; to highlight the education proposals in her intellectual production; to examine her actions as a cultural mediator; and to analyse the activity of this teacher at Centro de Criatividade. The time cut of this research covers the years 1955 to 2005. The initial mark refers to the year in which the teacher founded her “Little School of Music”, where she executed innovative practices for its time, which included theater and popular culture. The final mark is the year of 2005, with the staging of the show Opera of the Corn, during the third administration of Aglaé Fontes at Centro de Criatividade. The musical brought to the stage the representation of a “hasty” marriage, beliefs, dances, superstitions, June quadrilhas and the interference from the saints of the cycle. In a historical-cultural approach, this study has elected as main notions and concepts for dialogue: cultural capital and social capital, by Bourdieu (1989, 1996, 2005, 2006a); appropriations and representations, by Chartier (1990, 2009); memories, by Halbwachs (1990) and Pollak (1989, 1992); intellectuals and networks of sociability, by Sirinelli (1996); cultural mediator, by Gomes and Hansen (2016); and Art-Education, based on the understanding of Duarte Júnior (1986) and Barbosa (1989, 2002, 2016). This is a documental research, which used procedures of Oral History and has as main sources institutional documents, newspapers, photographs, audios, videos and oral records. The documents were found in the Central Archive and the Sectorial Archives at UFS; in the files of Historical and Geographical Institute of Sergipe; of the Central Library at UFS; of the Public Library Epifânio Dória; of the Central Library Jacinto Uchôa de Mendonça, at Tiradentes University (Unit); in the collections of the Education Post-Graduate Program at Federal University of Sergipe (PPGED/UFS) and of the Education Post-Graduate Program at Tiradentes University (PPED/Unit); and in private collections. I defend the thesis that teacher Aglaé d’Ávila Fontes is a mediator intellectual who teaches, produces knowledge, elaborates creative productions and develops cultural mediation practices, using art in different projects and educative processes, electing as thematic basis the appreciation of the popular culture from Sergipe.